Aerodynamic noise assessment for a vertical axis wind turbine using Improved Delayed Detached Eddy Simulation. (October 2019) - Su, Jie; Lei, Hang; Zhou, Dai; Han, Zhaolong; Bao, Yan; Zhu, Hongbo; Zhou, Lei
Abstract: This paper presents the results of the aerodynamic and aeroacoustic assessment for a vertical axis wind turbine (VAWT). The Improved Delayed Detached Eddy Simulation (IDDES) technique and Ffowcs Williams and Hawkings (FW-H) acoustic analogy method are adopted to simulate instantaneous flow field and to perform the noise prediction in the far field. The CFD model is verified against available experimental data for the power coefficient. The acoustic pressure spectra of thickness, loading, and quadrupole noise are presented, and the mechanisms and contributions of different noise are discussed. The effects of increasing rotational speed, receiver distance and turbulence intensity are studied. The results indicate that the thickness and loading noises are the dominant noise sources, while the influence of quadrupole noise is not negligible when the Mach number increases. Higher tip speed ratio and increased loads on blades will generate larger thickness and loading noise. In addition to the changes in lift and drag forces, higher turbulence intensity will make stronger interaction between vortex structures and blades, thereby induces a higher level of noise. It is concluded that this work could be exploited to design quieter vertical axis wind turbines and to locate the wind turbine position that minimizes noise pollution. Highlights: IDDES model has been used to calculate the turbulent flow field. The mechanisms of noise and influence of flow conditions are studied carefully. The higher turbulence intensity will cause drastic variation of static pressure. The increase of noise induced by turbulence intensity is small at high frequency.